Leader-Member Exchange as a Mediator of the Relationship Between Transformational Leadership and Followers' Performance and Organizational Citizenship Behavior - Wang, Hui; Law, Kenneth S.; Hackett, Rick D.; Wang, Duanxu; Chen, Zhen Xiong (Academy of Management Journal, 2005)
We developed a model in which leader-member exchange mediated between perceived transformational leadership behaviors and followers' task performance and organizational citizenship behaviors. Our sample comprised 162 leader-follower dyads within organizations situated throughout the People's Republic of China. We showed that leader-member exchange fully mediated between transformational leadership and task performance as well as organizational citizenship behaviors. Implications for the theory and practice of leadership are discussed, and future research directions offered.